Effectiveness of an Impella Versus Intra‐Aortic Balloon Pump in Patients Who Received Extracorporeal Membrane Oxygenation - Yuji Nishimoto; Hiroyuki Ohbe; Jun Nakata; Toru Takiguchi; Mikio Nakajima; Yusuke Sasabuchi; Toshiaki Isogai; Hiroki Matsui; Yukihito Sato; Tetsuya Watanabe; Takahisa Yamada; Masatake Fukunami; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background It is unclear whether an intra‐aortic balloon pump (IABP) or percutaneous ventricular assist device (Impella) in combination with extracorporeal membrane oxygenation (ECMO) is better. Methods Using the Japanese Diagnosis Procedure Combination database from September 2016 to March 2022, we identified inpatients who received an Impella or IABP in combination with ECMO (ECPella or ECMO+IABP group, respectively). The primary outcome was in‐hospital mortality, and the secondary outcomes included the length of hospital stay, length of ECMO, total hospitalization cost, complications, and durable mechanical circulatory support implantations. Propensity score matching was performed to compare the outcomes between the groups. Results Of 14 319 eligible patients, 590 (4.1%) received ECPella and 13 729 (96%) received ECMO+IABP. The mean age of patients was 65 years, 77% were men, and 57% had acute coronary syndrome. After propensity score matching, the patient characteristics were well balanced between the groups. The 14‐day mortality rate was lower in the ECPella group than in the ECMO+IABP group (28.0% versus 36.8%; risk difference, −8.2% [95% CI, −13.8 to −2.7]), whereas there was no significant difference in in‐hospital mortality between the groups (58.3% versus 56.6%; risk difference, 2.4% [95% CI, −3.5 to 8.2]). The ECPella group had a higher total hospitalization cost, increased renal replacement therapy during hospitalization, and more durable mechanical circulatory support implantations than the ECMO+IABP group. Conclusions This nationwide inpatient database study showed no significant difference in in‐hospital mortality between the groups, but ECPella was associated with a higher total hospitalization cost, increased renal replacement therapy during hospitalization, and more durable mechanical circulatory support implantations than ECMO+IABP.